THE DEVELOPMENT OF ETHNOPHYSICS BASED ENRICHMENT BOOK ON THE PROCESS OF MAKING BRICKS IN MUARO JAMBI REGENCY - Irma Fadilah; Fibrika Rahmat Basuki; Wawan Kurniawan; Jufrida Jufrida (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
This study aims to develop an ethnophysics-based enrichment book on the brick-making process in Muaro Jambi Regency in order to improve students' cognitive abilities. The research method used is Research and Development and refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were material experts, media experts, and students of class XII Science at SMAN 7 Kota Jambi. The research instruments used were interview guidelines, student characteristic questionnaires, observation sheets, expert validation sheets, and perception trial questionnaires. The data obtained were in the form of qualitative data which was analyzed continuously and intensively and quantitative data which were analyzed using descriptive statistics. This enrichment book is written in communicative language equipped with interesting pictures, data, and factual information on bricks in Muaro Jambi Regency. The results of the feasibility test by the material expert validators and the media experts in the first stage were 76% in the good category and in the second stage, it was 97% with the very good category. The results of the student's perception test showed that the ethnophysics-based high school physics enrichment book in the brick-making process in Muaro Jambi Regency was feasible to use with a percentage of 83% which was included in the very good category.